Clinical usefulness of myocardial scintigraphy in patients with vasospastic angina. Issue 5 (May 2020) - Sueda, Shozo
Highlights: Cardiac scintigraphy was useful to diagnose patients with vasospastic angina (VSA). Sensitivity of 201- thallium (Tl), 123 I beta-methyl 15-para-iodophenyl 3(R, S)-methylpentadecanoic acid (BMIPP), and of 123 I-metaiodobenzylguanidine was 57–77%. Sensitivity of left circumflex artery was significantly lower than other vessels. Tl or BMIPP cardiac scintigraphy for VSA as one of supplementary tools. Abstract: Background: Myocardial scintigraphy is defined as class IIb in the Japanese Circulation Society guideline for diagnosis of vasospastic angina (VSA). However, Caucasian guidelines had no classification of cardiac scintigraphy for diagnosis of VSA. Objectives: To clarify the clinical usefulness of myocardial scintigraphy, we analyzed the sensitivity and specificity of each cardiac scintigraphy. Methods: We extracted the 136 papers of myocardial scintigraphy from the PubMed database from 1980 to 2018 in patients with VSA. Finally we analyzed the 88 papers including 33 papers of 201- thallium (Tl), 10 papers of 123 I beta-methyl 15-para-iodophenyl 3(R, S)-methylpentadecanoic acid (BMIPP), 9 papers of 123 I-metaiodobenzylguanidine (MIBG), 4 papers of 99m Tc-sestamibi (MIBI: methoxy-isobutyl-isonitrile), and 2 papers of tetrofosmin to investigate the sensitivity and specificity of each tracer. Results: Tl, BMIPP, or MIBG cardiac scintigraphy were useful to diagnose patients with VSA, because sensitivity was 57–73%. Specificity was 55–83%. Sensitivity of left circumflex artery was significantly lower than other vessels. BMIPP imaging may be helpful for clinical course of VSA. However, myocardial scintigraphic abnormal findings may not always show the ischemic memory due to coronary artery spasm. Conclusions: Recent cardiologists do not perform hyperventilation tests or MIBG scintigraphy for diagnosis of coronary spasm. After understanding the flow of the times, cardiologists should use Tl or BMIPP myocardial scintigraphy for VSA as one of supplementary tools in the real world.